Application of Elliptical Properties in Building a Tomographic Image of an Inspected Object Using Multi-Element Ultrasonic Sensor Data: Chap.; Progress in Material Science and Engineering; Vol. 351 : Studies in Systems, Decision and Control (SSDC) - Shulgina Yu. V. Yulia Viktorovna; Shulgin E. M. Evgeny Mikhaylovich; Abouellail A. A. S. A. R. Ahmed Ali Sabri Ahmed Refaat; Kostina M. A. Maria Alekseevna; Terentjeva O. Yu. Oksana Yurjevna; Chang Jianglei (2021, 2021)
Title screen